Comparación de hallazgos tomográficos en pacientes con rinosinusitis crónica unilateral benigna y maligna en el Hospital Regional Docente de Trujillo en el período del 2015 al 2019 - Díaz Guevara, Eduardo (2021)
Chronic Rhinosinusitis with a prevalence of approximately 12%, within this group are those that only present symptoms on one side called Unilateral Chronic Rhinosinusitis, which represents a diagnostic challenge. A thorough evaluation of unilateral symptoms is important since neoplasms Sinonasal tumors can also present during its early stages with subtle symptoms that mimic an inflammatory pathology. The definitive diagnosis is determined by a complete evaluation of the stages that includes: clinical, imaging, surgical and histological manifestations. Computed tomography is currently the most used imaging technique for its initial assessment, there are elements highly suggestive of some sinus pathologies such as the formation of density of soft tissues, of unilateral location. Knowing how to classify it will lead to a different therapeutic outcome, from the performance of endoscopic surgery for the extraction of the sinus mass and / or the open approach for diseases that imply a greater commitment, in this project we intend to look for the tomographic characteristics of Benign Unilateral Chronic Rhinosinusitis and Maligna in the Otorhinolaryngology Service of the Trujillo Regional Teaching Hospital.